The burning world : a novel - Marion, Isaac, 1981- (The warm bodies series, 2017)
"The New York Times bestseller Warm Bodies captured hearts worldwide in twenty-five languages, inspiring a major film and a cult fandom. Now R the reluctant zombie continues his journey in this much-anticipated sequel. Being alive is hard. Being human is harder. But since his recent recovery from death, R is making progress. He's learning how to read, how to speak, maybe even how to love, and the city's undead population is showing signs of life. R can almost imagine a future with Julie, this girl who restarted his heart--building a new world from the ashes of the old one. And then helicopters appear on the horizon. Someone is coming to restore order. To silence all this noise. To return things to the way they were, the good old days of stability and control and the strong eating the weak. The plague is ancient and ambitious, and the Dead were never its only weapon. How do you fight an enemy that's in everyone? Can the world ever really change? With their home overrun by madmen, R, Julie, and their ragged group of refugees plunge into the otherworldly wastelands of America in search of answers. But there are some answers R doesn't want to find. A past life, an old shadow, crawling up from the basement"--